(untitled) (TEST Antologia di Diritto Pubblico, 2026)
The paper provides an introduction to the classic – and yet constantly relevant – theme of the interpretation of administrative acts. The author outlines some essential aspects, including those emerging from recent research on the adaptation of administrative measures carried out in various Italian universities, and he focuses in particular on the fact that the legal system does not lay down specific rules for the interpretation of administrative acts, as well as on the criteria most frequently applied by the courts.